Relationships of Religious Affiliation, Coping, and Support with Symptoms of Psychopathology in College Students - Edmondson, Daisy K (East Carolina University, 2023)
Background: Research has shown increases in mental health concerns in college students over the years that have worsened during the COVID-19 pandemic. Identifying factors that are protective in this context can aid in informing prevention and treatment efforts. Religiosity/religiousness has been shown to be generally beneficial regarding mental health, however, less is known about the mechanisms that account for that relationship. Some evidence indicates positive religious coping and religious support may be mechanisms. Little research has examined if religiousness is beneficial regarding mental health in college students during the pandemic, and if so, if positive religious coping and religious support are mechanisms. This study aimed to investigate the relationships of religiousness, positive religious coping, and religious support with symptoms of depression, anxiety, and post-traumatic stress disorder (PTSD) in college students during the COVID-19 pandemic. Specifically, the objectives of this study were to: 1) examine whether religious-affiliated college students have lower levels of symptoms of depression, anxiety, and/or PTSD compared to non-religiously affiliated students; and 2) if so, examine whether positive religious coping and religious support help account for the relationships observed between being religiously affiliated and lower symptoms. Method: This senior honors thesis project used pre-existing data from a cross-sectional online survey study that examined psychosocial and demographic risk and protective factors of PTSD during the pandemic (2020-21 academic school year) in a sample (N = 745) of undergraduate students from a large southeastern public university. The students were recruited using several methods: 1) Introductory Psychology courses, 2) a random sample of students, oversampled for male students and people of color, provided by the Survey Review and Oversight Committee, 3) emails to student organizations reflective of diversity requesting they share the study information with their members, and 4) emails to advisors, faculty, and other staff requesting they share the study with students. Participants in Introductory Psychology courses were given research credit for participating. All other participants were entered into a gift card raffle held each semester. Psychological symptomology was assessed with measures of 1) generalized anxiety disorder symptoms (Generalized Anxiety Scale-7); 2) depressive symptoms (Patient Health Questionnaire – 8); and 3) PTSD symptoms (PTSD Checklist for DSM-5). Religious affiliation, coping, and support were assessed with a modified version of the Brief Multidimensional Measure of Religiousness/Spirituality and Brief Religious COPE. Results: The correlation analyses showed the significant relationship of religious affiliation with psychopathology symptoms. The results further demonstrated that religious support considerably mediated the relationship of religiosity and anxiety, depression, and PTSD, but positive religious coping only mediated the relationship of religiosity and PTSD. Discussion: Results can aid in improving the identification of at-risk college students and the development of effective coping and support strategies.
Keywords: religiosity, college students, psychopathology